(untitled) (Brazilian Journal of Oceanography, 2006)
Colony size-frequency distributions of reef corals may be used to infer growth potential and population responses upon environmental changes. The present paper compares the size structure of colonies of Siderastrea stellata Verrill, 1868,among 11 sites, six of them distributed along a gradient of sediment deposition in Abrolhos, Bahia, Brazil (18º S). Results indicated that the population structure is likely to be influenced by local conditions, rather than large scale factors, such as latitude. The 11 distributions, however, showed higher frequencies of small size classes. Class 1 (up to 2.5 cm diameter) was always present and the frequency of colonies from size class 3 (10 cm diameter) tended to decrease in all sites. Comparison among the six Abrolhos sites showed that S. stellata has advantages at sites with intermediate sedimentation, where colonies attain larger sizes, probably, reflecting a higher survivorship over time. The present study showed that, despite the influence of environmental conditions on parameters of the populations such as size of colony, the life history strategy of S. stellata reflects a local adaptation that allows its development and survivorship in shallow waters and horizontal substrates, sites characterized by high mortality rates.